Developing An Attractive Employer Image in the Human Resources Marketing Plan - Rabah, Oukil; Emam, Ali Salman Mohammed (Journal of Cultural Analysis and Social Change, 2025)
In a highly competitive environment, companies seek various human resources (HR) marketing plan strategies to develop a strong employer image and become a more attractive employer. However, this has received little attention in the existing literature. This paper examines the components of the employer image central to a company’s HR marketing plan and how to communicate it effectively. This study concluded that developing the employer image is essential to HR marketing. This is because HR marketing plans focus on developing the organization into an attractive and competitive employer to attract and retain the best talent. Similarly, HR marketing must create a lasting, individualized relationship with each employee and build loyalty. Thus, an HR marketing plan is vital in enhancing the company's HR vision and strategy without deviating from the company's overall strategy, values, and vision. To reach the target population, there is a need to disseminate the employer's image through the proper tools and communication channels like mobile devices, the web, free press, online social media, customers, and school campuses.